1975
DOI: 10.1111/j.1365-2184.1975.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic‐microarchitectural Correlations in the Bone Marrow of the Mouse

Abstract: Transverse histologic sections of bone marrow obtained from mice that were sacrificed by perfusion fixation at intervals following tritiated thymidine injection were studied by means of radioautography. A kinetic gradient was demonstrated across the marrow section, with the highest proliferative rate in the subendosteal region. Megakaryocytes were shown to originate from the rapidly proliferating subendosteal cells. The immediate proliferating precursors of mature granulocytes were slowly proliferating cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Of course, migration into and/or away from different microenvironments is a well-known paradigm of differentiation in the embryo. In addition, progenitor migration between different extracellular microenvironments is an integral component of steady state differentiation in a variety of postnatal tissues, including the epidermis (40), intestinal crypts (41), germ cells (42,43), and even bone marrow (44,45). Frequently, the divergence of independent cell fates, i.e., commitment to one lineage vs another, or self-renewal vs differentiation, is intricately linked to the position of a given stem/progenitor cell relative to other cells in its microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, migration into and/or away from different microenvironments is a well-known paradigm of differentiation in the embryo. In addition, progenitor migration between different extracellular microenvironments is an integral component of steady state differentiation in a variety of postnatal tissues, including the epidermis (40), intestinal crypts (41), germ cells (42,43), and even bone marrow (44,45). Frequently, the divergence of independent cell fates, i.e., commitment to one lineage vs another, or self-renewal vs differentiation, is intricately linked to the position of a given stem/progenitor cell relative to other cells in its microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 MKPs are thought to reside near the bone surface in an "endosteal niche," where environmental cues encourage expansion, but suppress terminal maturation. [3][4][5][6] Polyploid MKs mature cytoplasmically, extrude proplatelets in association with sinusoidal vasculature, and shed platelets into the peripheral blood. [7][8][9] This process results in past-maturity "exhausted" MKs comprised of a nucleus with a thin layer of cytoplasm surrounded by a cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These results well supported the findings previously obtained in vivo that: (1) in murine BM, hematopoietic progenitors are distributed along the oxygen gradient, MRA progenitors being more concentrated where oxygen tension is Correspondence: P Dello Sbarba, Dipartimento di Patologia e Oncologia Sperimentali, viale GB Morgagni 50 -50134 Firenze, Italy; Fax: 390 5541 6908 Received 17 August 1999; accepted 16 December 1999 lower while CFU-GM reside preferentially in the best-oxygenated subendosteal areas, and (2) the probability of progenitors to be recruited into the mitotic cycle is inversely related to their distance from those areas. [6][7][8] In the experiments reported in this paper, liquid cultures of murine BM cells (BMC) supplemented with granulocyte/ macrophage colony-stimulating factor (GM-CSF) and interleukin-3 (IL3) were used to: (1) determine whether the inhibition of hematopoiesis in hypoxia is reversible; (2) characterize the hypoxia-maintained progenitors on the basis of their in vitro expansion potential, as measured by transferring hypoxic cultures to air; (3) compare these progenitors with progenitors detectable by the MRA assays. The results indicated that the hypoxia-dependent block of the expansion of hematopoietic clones is reversible.…”
Section: Introductionmentioning
confidence: 99%